Therapeutic vaccines for pancreatic cancer - (:unkn) unknown (Elsevier, 2019)
Pancreatic cancer is a consistently deadly malignancy with less than 5% survival at 5 years. To a great extent, this is because of metastatic potency, which is present in most patients who receive a diagnosis. Although the cancer can be resected surgically, local recurrence seems to happen within 1 year in 50%-80% of patients. This situation has led us to define oncolytic viruses focused on the tumor environment for effective treatment. Oncolytic viruses can kill cancer cells through various systems of activity, particularly by means of virus-initiated attack on the immune response against tumor cells. © 2019 Elsevier Inc. All rights reserved.
Keywords: Immunotherapy strategies; Oncolytic viruses; Pancreatic cancer; Vaccines